Manajemen Persediaan Bahan Baku pada Ayam Java di Kota Tarakan - Hidayat, Nurul; Meliana, Eva; Khasanah, Kholifatul (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The results of this study aim to help analyze inventory management at Ayam Java food stalls. In this study, qualitative methods were used by conducting direct interviews with Ayam Java food stall owners to obtain data used in inventory calculations. Based on interviews, the owner of the food stall admitted that he had never done inventory management. Therefore, this study tries to calculate the cost of ordering and storage costs of Java Chicken food stalls using the EOQ method, to assist owners in managing their inventory. The results showed that the EOQ method can help java chicken food stalls in minimizing the cost of ordering supplies. The EOQ method also helps owners know the optimal number and frequency of bookings. This is proven after calculation, there is a significant difference in booking costs